﻿Analysis of e-catalogue drug prices in the era of Universal Health Coverage in the Indonesian pharmaceutical industry - Satibi Satibi; Luthfi Kinanthi Kirana P; Mella Aziza P; Monica Hutasoit; Prasojo Pribadi (Pensoft Publishers, 2022)
Context: Since the implementation of the Universal Health Coverage (UHC) policy in Indonesia, the drug procurement system has changed to using the e-catalogue system. The impact of this policy change on the pharmaceutical industry in Indonesia is unclear and has not been widely studied. Objectives: This study analyzes the impact of the UHC policy on drug pricing by the pharmaceutical industry in Indonesia. Methods: This study collects data from 3 pharmaceutical industries that won the e-catalogue drug tender. Data on drug prices produced by these 3 industries in 2013 were taken from the Drug Price Ceiling List, while drug prices in 2015 and 2018 were obtained from the e-catalogue drug list. The drug price data is compared from year to year to see the trend of change and the magnitude of the change. Data were analyzed using a price index calculation adapted from the concept of Median Price Ratio (MRP) calculation to compare drug prices in 2013 with drug prices per each region in 2015 and 2018 in the Microsoft Excel Office application as a measuring tool. Results: There was a change in drug prices from the era before UHC (in 2013) and after the UHC era (in 2015 and 2018). There are drugs that have increased in price and some have decreased in price. The price increase ranged from 0.01-6.15 in 2015 and 0.01-6.46 in 2018. The price decrease ranged between 0.04-0.75 in 2015 and 0.01-0.83 in 2018. Conclusion: Drug prices from before the UHC era (2013 and 2015) to after UHC (in 2018) experienced a change in the form of an increase or decrease in price.